ANALYSIS OF THE IMPLEMENTATION OF THE E-S-QUAL MODEL ON THE EFFECTIVENESS OF DIGITAL ZAKAT: AN EMPIRICAL STUDY AT THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY OF NORTH SUMATRA - Afifah Adillah; Sambas Ade Kesuma; Khaira Amalia Fachrudin (CV. Radja Publika, 2025)
The main objective of this study is to examine the factors that influence the effectiveness of digital zakat using the E-S-QUAL theory. In the industrial revolution 4.0, digital payment of zakat has become an increasing trend, especially among the millennial generation. This study used a survey method with a non-probability sample of digital zakat users at the Faculty of Economics and Business, University of North Sumatra, resulting in 121 valid respondents. Data was collected through distributing questionnaires and analyzed using the SmartPLS tool. The analysis results show that efficiency and reliability variables have a positive and significant influence on the effectiveness of digital zakat, while fulfillment, privacy, speed, and system availability variables show no significant influence. The R-square for digital zakat effectiveness is 54.9%, showing the moderating influence of the independent variables on effectiveness. This study emphasizes the importance of improving digital service quality to increase user satisfaction and loyalty in zakat payment, as well as contributing to the literature on digital zakat in Indonesia.